CHEMICAL CHARACTERIZATION OF ESSENTIAL OIL FROM THE RHIZOMES OF KAEMPFERIA ROTUNDA L. BY GC/MS TECHNIQUE - AJAY KUMAR (International Journal of Pharma and Bio Sciences, 2014)
The essence oil from the fresh rhizomes of Kaempferia rotunda L. was isolated by water distillation and analyzed by gas chromatography-mass spectrometry (GC/MS) method. Fifty seven components were identified in the rhizomes oil, which accounted to 99.74% of the oil. The major components were endo-borneol (9.30%), dehydro iso androsterone acetate (9.12%), naphthalene, decahydro-1,1,4a-trimethyl-6-methylene-5-(3-methylene-4-pentenyl),[4aS-(4aα,5β,8aα)]- (9.03%), and β-phellandrene (7.08%), other prominent constituents were 2-propenoic acid, 3-(3-methoxyphenyl)-, ethyl ester (4.47%), a-pinene (3.39%), ethyl cinnamate, trans (3.15%), 2,6-octadienoic acid, 3,7-dimethyl-, methyl ester (2.90%) and camphene (2.89%).